Use the commutative property to rearrange the terms. Then simplify.

8ab−2b+ab−b

= 8ab + ab −


b

=

1 answer

To rearrange the terms using the commutative property and then simplify the expression 8ab2b+abb, you can follow these steps:

  1. Rearrange the expression: 8ab+ab2bb

  2. Combine like terms:

    • First, combine the terms with b: 2bb=3b
    • Now, the expression becomes: 8ab+ab3b
  3. Combine the ab terms: 8ab+ab=(8+1)ab=9ab

Now, we combine everything: 9ab3b

So, the final simplified expression is: 9ab3b

Similar Questions
  1. Given: 7x + 2 = 2 + 5x – 6Prove: x = –3 Given the equation 7x + 2 = 2 + 5x – 6, use the commutative property to rearrange
    1. answers icon 4 answers
  2. What is commutative property of addition?The commutative property of addition says we can change the order of the terms and the
    1. answers icon 0 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions